Optimization of the Dual Role of Housewives in the Economic Activities of Fishermen Communities in the Digital Era - Gano, Erwin; Khoiratun Nisak, Sayida; Wandi; Wargo; Kartika Devi, Erwina (CV. Civiliza Publishing, 2025)
The dual role of housewives in the fishing community of Mendahara Ilir Subdistrict is the primary focus of this study, which examines how they manage domestic responsibilities while simultaneously contributing to informal economic activities such as part-time work and small-scale enterprises. This study also highlights the practice of saving at Islamic banks as a strategy to enhance financial literacy and economic stability for fishing families. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that the dual role of housewives serves as a crucial pillar in maintaining family economic resilience, particularly amid the instability of husbands’ incomes. Economic activities carried out by housewives, such as betel nut peeling and home-based businesses, not only increase family income but also strengthen social solidarity within the community. Saving activities at Islamic banks align with religious values and contribute to sustainable family financial management. This study underscores the importance of policy support for women’s empowerment through skills training, access to capital, and market network expansion, alongside promoting inclusive financial services grounded in Islamic principles. In conclusion, the strategic involvement of housewives in both domestic and economic spheres significantly contributes to the sustainable socio-economic development of the fishing community